2002
DOI: 10.1034/j.1399-3038.2002.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

A similar high level of immunoglobulin A and immunoglobulin G class milk antibodies and increment of local lymphoid tissue on the duodenal mucosa in subjects with cow's milk allergy and recurrent abdominal pains

Abstract: In previous studies, we have reported endoscopic and histological alterations locally on the gastrointestinal (GI) tract associated with a gastrointestinal type of cow's milk allergy. In this study, we sought to further characterize endoscopic, and immunological findings in these children. We also hypothesized that the same type of immune responses might also be found in children with unexplained and recurrent abdominal pains. We did a gastroduodenoscopy for persistent GI symptoms, examined the mucosal histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
2
15
1
1
Order By: Relevance
“…1,2 Furthermore, it can occur in school-age children, 3,5,12 who frequently exhibited LNH of the colon, which is now considered a possible marker of FH in children. [3][4][5][6][7][8] On this basis, we performed a study in adults to search for a possible relation between FH, proctitis, and LNH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Furthermore, it can occur in school-age children, 3,5,12 who frequently exhibited LNH of the colon, which is now considered a possible marker of FH in children. [3][4][5][6][7][8] On this basis, we performed a study in adults to search for a possible relation between FH, proctitis, and LNH.…”
Section: Discussionmentioning
confidence: 99%
“…3 Others described LNH as an endoscopic marker of cow's milk allergy in children. [4][5][6][7][8] This prospective study showed that rectal bleeding and intestinal LNH can be caused by FH in adult patients.…”
mentioning
confidence: 85%
“…An association between CMA beyond infancy and recurrent abdominal pain has been reported 136. In addition, it has been reported that after clinical resolution and in absence of specific IgE, children with CMA may developed persistent abdominal pain 137.…”
Section: Immediate Allergic Reactionsmentioning
confidence: 99%
“…It was first described as an age-related finding in children of minimal significance, but further work noted a close association between LNH and the development of food allergies. It was shown that children with LNH were two to three times more likely to have non-IgE mediated allergies to food such as milk or cereal (Kokkonen et al, 1999) including high levels of IgG and IgA against milk proteins (Kokkonen et al, 2002), increased numbers of γδ T cells associated with the lymphoid follicles (Kokkonen et al, 2000), and increased CD4+ T cells with decreased T h1 cytokines (Bellanti et al, 2003). LNH was not found to be associated with Crohn’s disease or NOD2/CARD15 mutations raising speculation that LNH is not related to inflammatory disease, but may be a response to the microbial environment (Shaoul et al, 2006) as children with LNH showed a significant increase in number of bacteria adherent to the intestinal mucosa layer (Conte et al, 2006).…”
Section: Ilf Hyperplasia As a Sign Of Immune Dysfunctionmentioning
confidence: 99%